Perilaku ODHA dalam Pemeriksaan Berkala sebagai Upaya Perawatan dan Dukungan (Care and Support) di Kabupaten Pemalang - Handayani, Thukul Prasiddha; Shaluhiyah, Zahroh; Mustofa, Syamsulhuda Budi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2015)
ABSTRACTBehavior of PLWHA in Periodic Diagnostic Examination as Care and Support Effort in The Pemalang District;Improved quality of life of people living with HIV can be realized through care and support for PLWHA was periodic diagnostic examination behavior. PLWHA in Pemalang have routine examination as only 20%. This study aims to determine the factors that influence the behavior of people living with HIV in periodic diagnostic examination in Pemalang. This research was a quantitative study with cross sectional approach. Quantitative data collection techniques through questionnaire interviews where the number of respondents was 53 PLWHA. Data were analyzed using univariate analysis with frequency distribution, using the Chi-square bivariate and multivariate logistic regression. The results showed that the variables related to the behavior of people living with HIV in periodic diagnostic check was the last of education, income, knowledge, attitudes, availability and affordability, and HIV/AIDS disclosure. Multivariate analysis showed that knowledge (p value = 0.041) was the variable that has the most significant effect on the behavior of periodic diagnostic examination with OR of 3.927. The advice given to the government is to provide a comprehensive socialization of care and support include periodic medical examinations related what procedure should be done and the standard tariff for the examination.Keywords: PLWHA, Periodic Examination, Pemalang